Off-pump coronary artery bypass in congenital absence of pericardium. (August 2013) - Reddy, C Sukesh Kumar; Ali, Syed Nasheed; Raamaanuhadaasudu, C Kodhandapani; Parimi, Srinivas S; Reddy, T Ramakrishna; Reddy, Vijay Kumar
Off-pump coronary artery bypass involves precise manipulations for proper positioning the heart without causing hemodynamic compromise. Pericardial stay sutures exerting appropriate traction play an important role in off-pump surgery. We report a rare case in which a congenital pericardial defect was discovered after sternotomy in a patient undergoing off-pump coronary artery bypass.